The Great War seen from the air in Flanders fields, 1914-1918 - Stichelbaut, Birger; Chielens, Piet 1956- (Yale University Press, 2013)
A remarkable photographic record of World War One, its relentless progression and the destruction it wrought, as seen from the skies above Flanders Fields.